Simulation and Field Trial Results of Reconfigurable Intelligent Surfaces in 5G Networks - Ruiqi Liu; Jianwu Dou; Ping Li; Jianjun Wu; Yijun Cui (IEEE Access, 2022)
Recently, reconfigurable intelligent surfaces (RISs) are considered as a strong candidate for next generation wireless technologies, thanks to its advantage of being able to configure the wireless propagation environment in a cost-effective and energy-efficient way. Many literature study the theoretical aspects of RIS-assisted communication while prototyping and field trials are relatively scarce. A key step towards the standardization and commercialization of RISs is to complete comprehensive field trials in cellular networks, such as the 5th generation (5G) network. There are several typical deployment scenarios in 5G networks such as indoors, outdoors and mixed indoors and outdoors, where RISs can provide coverage to weak reception areas, enhance transmission robustness, fix coverage holes and increase the maximum available data rate. In this paper, a variety types of RIS prototypes are fabricated and tested with off-the-shelf 5G user equipments (UEs) in 5G networks to validate the performance gain introduced by RISs to typical deployment scenarios of 5G at different working frequencies. Some system-level simulations are also conducted for several typical scenarios to be used as a baseline to compare to the trial results, where all parameters are selected according to 5G standards. The experimental results confirm the feasibility and effectiveness of RISs to solve coverage issues and improve received signal qualities in 5G networks across different frequency ranges.